Analytical performance and standardization of four HCV RNA assays in China: an evaluation of sensitivity, precision, and genotype inclusivity - Yan, Hao; Xu, Bing; Zhang, Qinyi; Zhang, Lijun; Fang, Zhihan; Zhang, Huijun; Pan, Junhang; Xing, Wenge (Frontiers in Microbiology, 2025)
IntroductionAccurate, specific, and sensitive detection and quantification of hepatitis C virus (HCV) RNA are critical for diagnosing and managing HCV infections. This study evaluated and compared the performance of four commercially available HCV RNA quantification reagents using standardized serum panels, providing evidence-based insights for clinical applications.MethodsPerformance metrics, including analytical sensitivity, specificity, limit of detection (LOD), precision, genotype inclusivity (GT 1–6), and linearity, were assessed using seven distinct serum panels: basic, analytical specificity, seroconversion, analytical sensitivity, precision, genotype qualification, and linearity panels.ResultsAll reagents demonstrated 100% analytical sensitivity and specificity (95% CI: 79.95–100), with no cross-reactivity to common interfering substances or viruses. LOD values for reagents A, B, C, and D were 25, 50, 50, and 50 IU/ml, respectively. Intra- and inter-assay coefficients of variation (CVs) for HCV genotypes 1–6 ranged from 1.48 to 4.37% and 1.74 to 4.84%, respectively. Strong linear correlations (R2 > 0.95) were observed between measured and expected HCV RNA levels across all reagents.ConclusionThese reagents exhibit high sensitivity, specificity, precision, and accuracy for HCV genotypes 1–6, with a wide linear range, making them suitable for clinical diagnosis and monitoring of HCV infections.